IMPACT OF AQUEOUS EXTRACT OF NEEM LEAVES IN LOWERING BLOOD GLUCOSE AND LIPID PROFILE IN STZ INDUCED DIABETES MELLITUS MICE - A., Athraa H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the effect of aqueous neem (Azadirachta indica) leaves extract in reducing the sugar level of diabetic patients in male mice. The study included four groups and 15 mice for each group. The first group represented the control group. The mice in the remaining three groups were injected with streptozotocin (STZ) at dose of 50 mg/kg body weight. The second group was considered as the induced control group for diabetic patients for comparison, while the third group of diabetic patients received neem leaves extract 250 mg/kg of body weight, and the fourth group of diabetic patients was given metformin hydrochloride 250 mg/kg of body weight.  Measured Changes in blood glucose, blood triglycerides (TG), total cholesterol (TC), HDL, LDL cholesterol, VLDL cholesterol levels, and body weight. The results showed there was a significant decrease in blood glucose levels in diabetic groups and a decrease in cholesterol and triglycerides in groups treated with neem leaves extract compared with metformin hydrochloride. Thus, it can be concluded high blood sugar can be alleviated by treatment with an aqueous extract of Azadirachta indica leaves.